Leading in a VUCA World Integrating Leadership, Discernment and Spirituality - Kok, Jacobus; van den Heuvel, Steven C. (Contributions to Management Science, 2019)
This open access book brings together works by specialists from different disciplines and continents to reflect on the nexus between leadership, spirituality and discernment, particularly with regard to a world that is increasingly volatile, uncertain, complex, and ambiguous (VUCA). The book spells out, first of all, what our VUCA world entails, and how it affects businesses, organizations, and societies as a whole. Secondly, the book develops new perspectives on the processes of leadership, spirituality, and discernment, particularly in this VUCA context. These perspectives are interdisciplinary in nature, and are informed by e.g. management studies, leadership theory, philosophy, and theology.